تقييم كفاءة رئيسات الشعب التمريضية بتطبيق معايير الكفاءة العالمية في مشفى الأسد الجامعي والمشفى الوطني في اللاذقية - اصبيرة, ولاء (Latakia University Journal -Medical Sciences Series, 2016)
يعتبر دور رئيسة الشعبة التمريضية وكيفية عملها ضمن المؤسسات الصحية من المواضع التي شغلت العديد من الهيئات والمنظمات العالمية خلال العقدين السابقين, وذلك لما لهذا الدور من تأثير على العناصر التمريضية,ومقدمي الرعاية الصحية الآخرين, والمرضى, وبيئة المؤسسة الصحية ككل. ومن أجل أن تتمكن رئيسة الشعبة التمريضية من أداء مسؤولياتها لابد لها من بناء وتطوير مهاراتها الشخصية وكفاءتها القيادية باستمرار,وذلك بالاعتماد على معايير الكفاءة العالمية التي طورتها المنظمات والهيئات العالمية لتكون قاعدة أساسية لتقييم وتطوير كفاءة رئيسات الشعب التمريضية. بناء على هذه المعايير أُجريت هذه الدراسة والتي هدفت إلى تقييم كفاءة رئيسات الشعب التمريضية بتطبيق معايير الكفاءة العالمية في مشفى الأسد الجامعي والمشفى الوطني في اللاذقية.أُجريت الدراسة في مشفى الأسد الجامعي والمشفى الوطني. حيث تكونت العينة من 21 رئيسة شعبة تمريضية, و80 ممرضة من كلا المشفيين. وكانت من أهم النتائج وجود توافق في وجهات نظر الممرضات ووجهات نظر رئيسات الشعب التمريضية في كلا المشفيين في تطبيق معايير الكفاءة العالمية. Introduction:The nurse manager role and how it is carried out in healthcare organizations has been an important topic which had emphasized by many international organizations and institutions during the past two decades. Thus, this role had impact on nursing staff, other healthcare providers, patients and on healthcare environment as whole. To carry out her duties, nurse manager needs to build up and improve her personal skills and leadership competencies continuously. This by depending on international competency standards which developed by international organizations and institutions to be the basic to assess and improve nurse managers competency. Depending on these standards, this study was conducted and aimed to assess nurse managers' competency in implementing international competency standards in Al- Assad university hospital and Al- Wattany hospital at Lattakia.Thestudy was conducted on Al- Assad university and Al- Wattany hospitals at Lattakia. Whereas, The study sample consisted of 21 nurse managers , and 80 nurses from two hospitals. The main results ofthis study was that there was agreement between nurses 'viewpoints and nurse managers' viewpoint in both hospitals on nurse managers' implementation of international competencies standards.